2018
DOI: 10.15406/mseij.2018.02.00050
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Water Effluents Using Silver Nanoparticles

Abstract: The water from industries with potential hazardous organic matters when discharged into the water bodies cause undesirable effects to the environment, aquatic life and human health. So it is necessary to treat waste water prior to their disposal. Degradation of organic pollutants is a major concern in the present scenario due to its stability, fastness to sunlight, resistance to degrading agents or microbial attack. It is mainly achieved by silver metal nanoparticles synthesised by green route. Degradation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 71 publications
(92 reference statements)
0
1
0
Order By: Relevance
“…According to Prasad et al nanoparticles operate as nanosorbents for the removal of heavy metals and organic contaminants, and when doped with additional metals, their activity increases significantly (Prasad et al 2019). Beena Mathew et al concluded that thephotocatalytic activity of silver nanoparticles improves the efficiency of dye removal in wastewater (Mathew 2018). Silver nanoparticles developed by Mohammed TahaMoustafa et al exhibit strong antibacterial action against both gramme positive and gramme negative microorganisms (Moustafa 2017).…”
Section: Discussionmentioning
confidence: 99%
“…According to Prasad et al nanoparticles operate as nanosorbents for the removal of heavy metals and organic contaminants, and when doped with additional metals, their activity increases significantly (Prasad et al 2019). Beena Mathew et al concluded that thephotocatalytic activity of silver nanoparticles improves the efficiency of dye removal in wastewater (Mathew 2018). Silver nanoparticles developed by Mohammed TahaMoustafa et al exhibit strong antibacterial action against both gramme positive and gramme negative microorganisms (Moustafa 2017).…”
Section: Discussionmentioning
confidence: 99%